2019
DOI: 10.22159/ajpcr.2019.v12i12.35589
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Robusta Coffee (Coffea Canephora L.) Leaves to Staphylococcus Aureus and Escherichia Coli

Abstract: Objective: This research aims to analyze the ability of robusta coffee leaves fraction extract to inhibit the growth of Staphylococcus aureus and Escherichia coli and also determine the minimum inhibitory concentration (MIC). Methods: Antibacterial activity evaluated by the disc diffusion method observed in four types of fraction of extract robusta coffee leaves (n-hexane, ethyl acetate, ethanol, and water). Each extract divided into three various concentrations, 5%, 10%, and 15%. Determination of antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Meanwhile, caffeine has antibacterial (Pruthviraj et al 2011;Nonthakaew et al 2015) and antifungal effects (Nonthakaew et al 2015). Muslim and Dephinto (2019) added that extract of coffee leaves has antibacterial effect. Nonthakaew et al (2015) reported that bacterial and fungal growth was affected by caffeine at 2 and 5 mg/mL, whereas caffeine in this research was 1.25 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, caffeine has antibacterial (Pruthviraj et al 2011;Nonthakaew et al 2015) and antifungal effects (Nonthakaew et al 2015). Muslim and Dephinto (2019) added that extract of coffee leaves has antibacterial effect. Nonthakaew et al (2015) reported that bacterial and fungal growth was affected by caffeine at 2 and 5 mg/mL, whereas caffeine in this research was 1.25 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…In the Eschechia coli bacteria test from the ethyl acetate fraction, the zone of inhibition was 13.12; 12.08 ; 17.28 mm with concentrations of 5, 10, and 15%. In the Escherichia coli test of N-Hexane, the zone of inhibition was 10.7; 12.07 ; 13.31 mm with concentrations of 5, 10, and 15% (7).…”
Section: Coffea Canepora Lmentioning
confidence: 97%
“…Coffee is a plant or tree that is efficacious for anti-cellulite, exfoliating dead skin cells, anti-aging, anti-inflammatory, antioxidant, and anti-acne [12][13][14]. The previous research reported that C. canephora leaves have antibacterial activity but there has been no research on antimicrobial tests against S. aureus and P. acnes from robusta coffee seeds [15]. Based on the reported literature, coffee contains volatile and non-volatile compounds.…”
Section: Introductionmentioning
confidence: 99%